The distribution of rest periods affects performance and adaptations of energy metabolism induced by high-intensity training in human muscle - Parra, J.; Cadefau, J. A.; Rodas, G.; Amigo, N.; Cusso, R. (Acta Physiologica Scandinavica, 2000)
The effect of the distribution of rest periods on the efficacy of interval sprint training is analysed. Ten male subjects, divided at random into two groups, performed distinct incremental sprint training protocols, in which the muscle load was the same (14 sessions), but the distribution of rest periods was varied. The 'short programme' group (SP) trained every day for 2 weeks, while the 'long programme' group (LP) trained over a 6-week period with a 2-day rest period following each training session. The volunteers performed a 30-s supramaximal cycling test on a cycle ergometer before and after training. Muscle biopsies were obtained from the vastus lateralis before and after each test to examine metabolites and enzyme activities. Both training programmes led to a marked increase (all significant, P < 0.05) in enzymatic activities related to glycolysis (phosphofructokinase - SP 107%, LP 68% and aldolase - SP 46%, LP 28%) and aerobic metabolism (citrate synthase - SP 38%, LP 28.4% and 3-hydroxyacyl-CoA dehydrogenase - SP 60%, LP 38.7%). However, the activity of creatine kinase (44%), pyruvate kinase (35%) and lactate dehydrogenase (45%) rose significantly (P < 0.05) only in SP. At the end of the training programme, SP had suffered a significant decrease in anaerobic ATP consumption per gram muscle (P < 0.05) and glycogen degradation (P < 0.05) during the post-training test, and failed to improve performance. In contrast, LP showed a marked improvement in performance (P < 0.05) although without a significant increase in anaerobic ATP consumption, glycolysis or glycogenolysis rate. These results indicate that high-intensity cycling training in 14 sessions improves enzyme activities of anaerobic and aerobic metabolism. These changes are affected by the distribution of rest periods, hence shorter rest periods produce larger increase in pyruvate kinase, creatine kinase and lactate dehydrogenase. However, performance did not improve in a short training programme that did not include days for recovery, which suggests that muscle fibres suffer fatigue or injury.